Production Potentials and Economic Feasibility of Improved Sugarcane Based Cropping Systems - S.N. Singh, A. K. Sah, R.K. Singh, V.K. Singh, Rakesh K. Singh, Om Prakash (Indian Journal of Extension Education, 2022)
..